Correlation of Breast Lump Mammographic and Sonomammographic Findings with Histopathological Diagnosis - Goswami KG; Bansal A; Agrawal SK; Agarwal B; Thakral RK; Sharma AC (Asian Journal of Medical Radiological Research, 2020)
Background: Breast cancer is the second most common cancer in Indian women. Early detection, diagnosis, and treatment is possible by screening women with breast lumps. Most commonly used screening methods are Mammography and Sonomammography, with histopathological confirmation done in suspected cases. The aim of this research was to find out the most accurate method of screening for cancer in females presenting with breast lumps.Subjects and Methods: We enrolled 53 females with age over 35 years presenting with palpable breast lump. All patients were subjected to Mammography, Sonomammography, and Fine Needle Aspiration Cytology. Findings of mammography and sonomammograohy were correlated with Fine needle aspiration cytology (as gold standard for cancer diagnosis) to find out the most sensitive, specific and accurate screening methodology.Results:The sensitivity and specificity for cancer diagnosis by mammography was 77% and 98% respectively, as compared to 56% and 97% for sonomammography. The sensitivity and specificity of both methods combined was 100% and 97% respectively. In younger patients with mammographically dense breasts, sonomammography performs better for detection and diagnosis.Conclusion: Mammography and Sonomammography are individually effective diagnostic modalities for detection of breast cancer. Detection of breast carcinoma is higher by mammography in comparison to Sonomammography; however, the accuracy significantly improves when both methods are combined. Sonomammography is better in comparison to mammography for detecting lesions in mammographically dense breast.